STRATEGI KOMUNIKASI ORGANISASI SERIKAT PEKERJA NASIONAL PT. PARKLAND WORLD INDONESIA DALAM MENINGKATKAN KESEJAHTERAAN KARYAWAN: Studi Kasus Di PT. Parkland World Indonesia - Laksana, April; Fajarwati, Noerma Kurnia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
Labor is an important element in the development process. Labor development is directed at improving the quality and contribution of the workforce. The more labor, the more demands / problems from workers to the company will be. The purpose of establishing a Tongue Workers Union or as a mediation between workers and companies is to fight for and protect the rights of workers. The purpose of this study was to find out the Communication Strategy used by the National Workers Union in improving the welfare of employees of PT Parkland World Indonesia and To find out the inhibiting factors and drivers of the National Workers Union in improving the welfare of employees of PT Parkland World Indonesia. This study uses a methodology of case studies or case studies. The results of this study are that PT Parkland World Indonesia's National Trade Union organization communication strategy in improving employee welfare has been effective. It is seen from the lack of employees conducting demonstrations to companies demanding wage increases because the National Labor Union negotiates with companies in an effort to increase wages, but in the process communication also found obstacles that occurred in the field, for this reason the task of the National Labor Union of PT Parkland World Indonesia was to give trust to its members